The Determinants of Effective Green Business Process Management Evidence from Malaysian Manufacturing Firms - Nadarajah, Subashini (2012)
Environment protection is the buzz word in today’s corporate world. Corporations are required to implement pro-environment policies and practices to create and sustain competitiveness. To this end, green business process management (GBPM) is recognized one of the best managerial practice to protect the environment. The fundamental argument of this thesis is that whilst GBPM is contingent upon a corporation’s internal practices, the role of upstream suppliers in facilitating effective GBPM is pivotal. Efficient integration of internal and external green business practices could accentuate GBPM. External green business practices here refer to upstream suppliers’ green business practices. In essence corporations with GBPM would need to select, monitor and collaborate with suppliers (both upstream and downstream) of green practice nature. A mismatch between green advocating corporation and non-green based suppliers would lead to ineffective GBPM. This research was undertaken with the aim of examining the influence of green supplier selection, green supplier monitoring and green supplier collaboration to effective green business process management amongst Malaysian manufacturing corporations. Using the resource based view theoretical lens, a survey was done on 122 manufacturing corporations in Malaysia. The empirical analysis using the Partial Least Square (PLS) modeling technique revealed that green supplier monitoring and green supplier selection has a significant influence toward effective GBPM in the sample manufacturing corporations. The influence of green supplier collaboration on the other hand is insignificant. Several key policy recommendations are proposed to facilitate and enhance the roles of the three factors toward effective GBPM.